Entrepreneurship and Business Ethics: Implications on Corporate Performance - Ogbari, Mercy Ejovwokeoghene; Oke, Adunola Oluremi; Ibukunoluwa, Adeyemo A.; Ajagbe, Musibau Akintunde; Ologbo, Andrew Cat (International Journal of Economics and Financial Issues, 2016)
The purpose of this research is to examine the impact of business ethics on corporate performance. The hypotheses were set using four main objectives. Data were obtained using both primary and secondary sources. The primary data was obtained by using a structured questionnaire design. Whilst relevant published and unpublished literature provided the secondary data. The total number of questionnaires distributed was 286, out of which 260 were returned. Descriptive and inferential statistics were used for the data analysis. The statistical tools used include frequency table, multiple regression analysis, analysis of variance, correlation analysis. The results showed that there was a significant relationship between the ethical practices of organizations and their corporate performance. Moreso, the employees of the sampled organizations concurred that their organization is highly ethical. Based on these findings, the authors profer the need for clearly defined ethics within corporate organizations as this would guide the employees in their day to day conduct. Keywords: Entrepreneurship; Business Ethics; Employee Behaviour; Entrepreneurial Performance; Nigeria JEL Classification: L26